Targeting Oncogenic Mutant p53 for Cancer Therapy - Parrales, Alejandro; Iwakuma, Tomoo (Frontiers in Oncology, 2015)
Among genetic alterations in human cancers, mutations in the tumor suppressor p53 gene are the most common, occurring in over 50% of human cancers. The majority of p53 mutations are missense mutations and result in the accumulation of dysfunctional p53 protein in tumors. These mutants frequently have oncogenic gain-of-function (GOF) activities and exacerbate malignant properties of cancer cells, such as metastasis and drug resistance. Increasing evidence reveals that stabilization of mutant p53 in tumors is crucial for its oncogenic activities, while depletion of mutant p53 attenuates malignant properties of cancer cells. Thus, mutant p53 is an attractive druggable target for cancer therapy. Different approaches have been taken to develop small molecule compounds that specifically target mutant p53. These include compounds that restore wild-type conformation and transcriptional activity of mutant p53, induce depletion of mutant p53, inhibit downstream pathways of oncogenic mutant p53, and induce synthetic lethality to mutant p53. In this review article, we comprehensively discuss the current strategies targeting oncogenic mutant p53 in cancers, with special focus on compounds that restore wild-type p53 transcriptional activity of mutant p53 and those reducing mutant p53 levels.